Reflections on JBCR Growth and Development - Charles R. Baxter (Journal of Burn Care & Rehabilitation, 1983)
Diabetes mellitus causes vascular dysfunction, immune dysregulation, and cellular abnormalities. Prior studies suggest worse outcomes in burn patients with diabetes mellitus but are limited by single- institution studies and small sample sizes. National databases like the Burn Care Quality Platform (BCQP) can provide higher-powered multi-institutional datasets to determine outcomes otherwise unseen. Using the BCQP, adult burn patients admitted for burn care from 2016 to 2018 were retrospectively reviewed for diabetes status. Primary outcomes were time to 95% wound closure. Secondary outcomes were hospital and intensive care unit (ICU) length of stay (LOS), rates of acute respiratory distress syndrome (ARDS), ventilator-associated pneumonia (VAP), central line-associated bloodstream infection (CLABS), operative intervention rates, and in-hospital mortality. Diabetic patients had longer wound closure time (25 versus 22 days, p = 0.0006) and more operative procedures (15.8 versus 1.3, p < 0.0001) than non-diabetic patients. Diabetic patients also had longer hospital LOS (8 versus 5 days, p < 0.0001) and higher mortality (5.7% vs. 4.1%, p = 0.045) than non-diabetic patients, with no differences in ARDS, VAP, or CLABSI. On multivariable analysis, diabetes mellitus itself was not an independent predictor of complications or mortality, but early hyperglycemia was the strongest modifiable predictor of ARDS, VAP, and CLABSI. Overall, diabetes mellitus was associated with delayed wound healing, longer hospital LOS, and ICU LOS. Acute complications were driven by early hyperglycemia following admission and injury severity, highlighting early glycemic optimization in burn care.